Constructing meanings of luxury in Airbnb - Farmaki, Anna; Spanou, Elena; Christou, Prokopis A. (My University, 2021)
Purpose: Following Airbnb’s recent turn to the luxury market, this paper aims to explore how Airbnb hosts construct meanings of luxury as enacted in their hosting practices. Design/methodology/approach: Semi-structured interviews with 46 Airbnb hosts were undertaken using purposing sampling. Findings: Study findings reveal that social and personal meanings of luxury manifest in host practice, with “home feeling” representing the epicentre of the luxury peer-to-peer (P2P) accommodation experience. Research limitations/implications: Although this study draws from host views, it represents a first attempt to empirically examine perceptions and applications of luxury within P2P accommodation. The study provides a conceptual framework which may serve as a point of departure for further research into which luxury service dimensions guests value. Practical implications: The findings of the study carry implications to the wider hospitality context. Specifically, hospitality practitioners need to reconceptualize luxury hospitality provision to promote a “homotel” accommodation model which highlights the offering of physical and social luxury dimensions in addition to elements of personalized service and home-like hedonic benefits. Originality/value: The study offers a conceptual framework of the luxury P2P accommodation servicescape, which identifies two distinct luxury offerings that may be informative to both P2P accommodation providers and hospitality practitioners.
Keywords: Luxury; Airbnb; Peer-to-peer accommodation; Host practice